THE SENSATIONAL LITERATURE OF SCANDINAVIAN EUROPE - Petre Gheorghe BÂRLEA (Diversitate si Identitate Culturala in Europa)
An interesting phenomenon is noticeable in world literature: apart from the emergence of the odd/some writer of genius in various parts of the world, it is quite common to see a sizeable group of writers from a certain geographic area take the literary scene by storm, with books emanating the same atmosphere, which would serve to justify, by way of example, the so - called “theory of cultural rifts”, advanced by the studies on world history.